Measurements of cosmic-ray energy spectra with the second CREAM flight - MAESTRO, PAOLO; H. S. AHN; P. ALLISON; BAGLIESI, MARIA GRAZIA; L. BARBIER; J. J. BEATTY; BIGONGIARI, GABRIELE; T. J. BRANDT; J. T. CHILDERS; N. B. CONKLIN; S. COUTU; M. A. DUVERNOIS; et al. (Nuclear Physics B - Proceedings Supplements, 2009)
During its second Antarctic flight, the CREAM (Cosmic Ray Energetics And Mass) balloon experiment collected data for 28 days, measuring the charge and the energy of cosmic rays (CR) with a redundant system of particle identification and an imaging thin ionization calorimeter. Preliminary direct measurements of the absolute intensities of individual CR nuclei are reported in the elemental range from carbon to iron at very high energy.